Performance of Assessment Relationship between Characteristics Student Learning Style and Lecturer's Teaching Method Using Fuzzy Inference System: A Case Study Department of Information Technology State Polytechnic of Samarinda - Rihartanto Rihartanto; Arief Bramanto W. P. (International Journal of Computing and Informatics (IJCANDI), 2016)
Baseline characteristics of students’ knowledge in the concept of learning technology is required. One is the student's learning style characteristics including attitudes, cognitive and psychomotor or skills. Then, characteristics of learning styles based approach sensory preferences, including visually, auditory, and kinesthetic or learning by doing/movement and touch. In this study, methods of teaching as a learning process consisting of multimedia-based teaching, lectures, demonstrations, problem solving, discussion, exercises (drill), case studies, frequently asked questions, and experiment. Three types of questionnaire consisting of the distribution characteristics of student learning styles, the tendency of students learning methods, and the tendency of lecturers teaching methods have been implemented. In order to determine the grade level of each questionnaire with grade visual (V), auditory (A), kinesthetic (K), auditory-kinesthetic (AK), and visual-auditory (VA) have been exploited. The results showed that the relationship between these three variables has yielded a value of 68.2%. It means that the FIS method could be used in order to assess the performance relationship.